Exome Sequencing Identifies Compound Heterozygous Mutations in SCN5A Associated with Congenital Complete Heart Block in the Thai Population - Thongnak C. (2017)
© 2016 Chuphong Thongnak et al. Background. Congenital heart block is characterized by blockage of electrical impulses from the atrioventricular node (AV node) to the ventricles. This blockage can be caused by ion channel impairment that is the result of genetic variation. This study aimed to investigate the possible causative variants in a Thai family with complete heart block by using whole exome sequencing. Methods. Genomic DNA was collected from a family consisting of five family members in three generations in which one of three children in generation III had complete heart block. Whole exome sequencing was performed on one complete heart block affected child and one unaffected sibling. Bioinformatics was used to identify annotated and filtered variants. Candidate variants were validated and the segregation analysis of other family members was performed. Results. This study identified compound heterozygous variants, c.101G > A and c.3832G > A, in the SCN5A gene and c.28730C > T in the TTN gene. Conclusions. Compound heterozygous variants in the SCN5A gene were found in the complete heart block affected child but these two variants were found only in the this affected sibling and were not found in other unaffected family members. Hence, these variants in the SCN5A gene were the most possible disease-causing variants in this family.